Mitigation Measures to Address Soiling Effect in Solar Photovoltaic System Performance in Kuwait - Althuwaini, Yaqoub E. (Science and Technology - Recent Updates and Future Prospects Vol. 2, 2024)
The present study primarily focused on Mitigation measures to address the soiling effect in solar photovoltaic system performance in Kuwait. The solar energy system has developed significantly in recent years, but a system’s lifetime may be impacted directly or indirectly by soiling, which is the accumulation of particles on a PV module’s surface. The Gulf Cooperation Countries have the advantages of fundamental characteristics and abundant natural resources due to the high proportion of solar radiation, which helps to expand the transition to renewable energy, especially in solar projects. The Kuwait location was chosen for this research because of its high dust levels and average daily sunshine of 9.4 hours. The Metrological Department of the Directorate General of Civil Aviation in Kuwait reports that the average amount of dust that falls over Kuwait ranges from 20 to 60 tons per square kilometer per month, which adds up to approximately 1 million tons per year. The soiling map of Kuwait was then created using PVsyst software. A theoretical and mathematical model for 100 MW was developed based on many environmental and technical parameters. The model was run with Kuwait parameters and 100 MW solar PV power plant capacity. Several methods have been adopted and investigated to mitigate dust from PV panels. Mitigation strategies fall into two broad categories: prevention and restorative. The results show that more than 25% of total generated electricity could be lost annually without any mitigation strategy. Furthermore, the efficiency loss could increase by around 50% during the seasons with sandstorms and high soiling rates. Additionally, manual and automatic cleaning methods were found to increase energy production from 112,092 MWh to 207,300 MWh. Moreover, manual cleaning reduced energy costs by 4.9%, but automated cleaning resulted in a 17.34% higher energy-saving cost than a system without cleaning. In addition, when using the automatic cleaning system, the payback period was reduced from 9.22 to 7.86 years. Therefore, an automated cleaning system is recommended for use in Kuwait. In general, FPVs are viable alternatives, and they are worth installing in the region of middle east Asian countries.